Health Guidelines for Travel Abroad - Lohr, Jason (Prim Care, 2018)
Most travel medical care is provided by patients’ primary care physicians; only 10% of international travelers visit a travel clinic. The main purposes for travel include vacationing, visiting friends and family, business, and for educational purposes. The purposes of the pretravel consultation are to estimate risk and provide recommendations to mitigate risk.